Book Review: Mesozoic Geology and Paleontology of Misool Archipelago, Eastern Indonesia - Herman Darman (Ikatan Ahli Geologi Indonesia, 2014)
Scientific publications on the Mesozoic of Eastern Indonesia are very rare. This region is relatively remote and accesses to outcrops are generally difficult. Recent publications are predominantly published by petroleum companies based on their subsurface data. It is important to integrate subsurface and outcrops to understand the geology of the area. Hasibuan’s research on becomes important piece of information because he worked entirely based on outcrop data.